The Chile of Lagos: the challenge of a new democratic path - Aggio, Alberto (FCL-UNESP Laboratório Editorial, 2007)
The text analyses synthetically the transition process towards democracy in Chile and observes how the central elements of this process appeared in the Chilean recent elections. Through this approach, it also analyses the conditions present in the first presidential election in two phases realized in Chile as well as the characteristics and limits of the two main candidatures: Ricardo Lagos and Joaquín Lavín.